PENGARUH GAYA HIDUP HEDONISME TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PERGURUAN TINGGI DI BANDUNG - Hatimatunnisani, Hani; Pradipta , Aurora; Zahra , Wulan; Amalia , Marizca; Putri , Linda (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Hedonism is where a person must seek as much happiness as possible and avoid painful feelings. Pleasure and personal satisfaction without long-term considerations often characterize a hedonistic lifestyle. This research aims to determine the influence of a hedonistic lifestyle on financial management among students at universities in Bandung. Quantitative methods are used to analyze this. The result of a questionnaire on 100 respondents showed that there was a significant influence between a hedonistic lifestyle on financial management, but the influence was only 6.8%. The result of the interviews illustrate that students are starting to understand that an excessive lifestyle can have a negative impact if it is not balanced with wise financial management knowledge. Even though some students are indicated to have a hedonistic lifestyle, they can still control and manage their personal finances well.